FUTURE MARKETING IN B2B SEGMENT: INTEGRATING ARTIFICIAL INTELLIGENCE INTO SALES MANAGEMENT - Koldyshev Maxim Vladimirovich (International Journal of Innovative Technologies in Economy, 2020)
The technological phenomenon of artificial intelligence transforms B2B marketing and approaches to the formation of product value, sales and service. The case study allowed the author to examine and summarize the experience of large companies in integrating artificial intelligence into the sales management system, marketing and service. The article identified three problems of B2B companies’ sales system: incomplete, unreliable data, lack of interaction between marketing and sales systems, dynamic growth of personal data volume. The study proves economic efficiency of the integration of artificial intelligence, which solves these problems. The future of marketing was identified based on the latest trends in the B2B segment. In the future, industrial marketing will be determined by the accuracy, reliability of customer information, a high level of accuracy of demand forecasts, a shortened cycle of trade agreements, increasing level of effectiveness of cooperation between marketing and sales departments. The integration of artificial intelligence into sales management will finally complete the era of digital marketing in the B2B segment and will be the beginning of the era of “human” marketing. The latter will mean that in the context of a regulated digital private B2B data market, marketing will be focused on human needs with an accurate predictable understanding of customer needs.